Effectiveness of virtual reality media based on local wisdom: Indigenous Baduy Tribe, Kasepuhan Citorek and Kesepuhan Neglasari Banten Indonesia - Adiputra, Dede Kurnia; Japar, Muhammad; Muslim, Suyitno (Edelweiss Applied Science and Technology, 2024)
The application of Virtual Reality media based on local wisdom in learning Natural and Social Sciences for grade IV elementary school students, with an emphasis on the culture of the Baduy Tribe, Kasepuhan Citorek, and Kesepuhan Neglasari in Banten, Indonesia. This study is to assess how virtual reality technology can improve students’ understanding and interest in Natural and Social Sciences materials related to local wisdom and customs. The results of the study indicate that the virtual reality media applied is effective in significantly improving students’ understanding. The average N-Gain value of 0.85 indicates the success of the media in achieving its goals. It can be concluded that the use of virtual reality not only deepens students’ understanding of Natural and Social Sciences topics related to local wisdom, but also motivates them to be more active in the learning process.